2018
DOI: 10.1126/science.aan2433
|View full text |Cite
|
Sign up to set email alerts
|

Giant polarization in super-tetragonal thin films through interphase strain

Abstract: Strain engineering has emerged as a powerful tool to create new states of known materials with excellent performance. Here, we show a general and practically realizable method via interphase strain to obtain a new super tetragonality providing giant polarization. This method is illustrated for the case of PbTiO3, where we report a c/a ratio of up to 1.238 in epitaxial composite thin films, compared to that of 1.065 in bulk PbTiO3. These thin films of super-tetragonal structure possess an unprecedented giant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
155
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 60 publications
10
155
0
Order By: Relevance
“…Ferroelectrics have long been studied due to its switchable polarizations and thus are promising for a plethora of applications such as in electromechanical systems, [1,2] multiferroics systems, [3][4][5][6][7] and memory/energy storage systems. [8][9][10][11][12][13][14][15] Ferroelectric materials, in particular, perovskites ferroelectrics [8] such as Pb(Zr,Ti)O 3 (PZT), [16][17][18] BaTiO 3 , [19][20][21] and SrBi 2 Ta 2 O 9 [22,23] have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectrics have long been studied due to its switchable polarizations and thus are promising for a plethora of applications such as in electromechanical systems, [1,2] multiferroics systems, [3][4][5][6][7] and memory/energy storage systems. [8][9][10][11][12][13][14][15] Ferroelectric materials, in particular, perovskites ferroelectrics [8] such as Pb(Zr,Ti)O 3 (PZT), [16][17][18] BaTiO 3 , [19][20][21] and SrBi 2 Ta 2 O 9 [22,23] have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…b Magnetic structure in the T phase rendering C-type antiferromagnetism (AFM-C); green arrows represent atomic magnetic moments and their orientation. c Examples of substrates in which to grow BCO thin films displaying the effects predicted in this study; other well-known materials exhibiting super-tetragonal phases are shown for comparison[19,22]. "SE" stands for magnetic super-exchange interactions.…”
mentioning
confidence: 96%
“…Common strategies employed to synthesize bettered multiferroic materials include doping [14,15], solid solutions [16,17], and strain engineering in thin films [1,18]. Through epitaxial strain is actually possible to create new multiferroic materials in the laboratory that ex- * Corresponding Author hibit giant electric polarization and unexpected magnetic spin ordering [19][20][21]. An illustrative example is given by BiFeO 3 (BFO), in which large spontaneous polarization and ferromagnetism (FM) have been observed under moderate compressive biaxial strains at room temperature [22,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, strain enhances the charge carrier mobility in modern electronics [2][3][4]. It allows the tuning of the optical properties of materials [5][6][7], can confer them with a ferroelectric nature [8,9], or even make them better superconductors [10]. Despite these successes, strain engineering is still a largely unexplored field considering the huge parameter space available; indeed, stress is characterized by six parameters (three axial components and three shear components, defining the stress tensor) which, in principle, can be continuously and independently varied over many orders of magnitude to optimize the functional properties of materials [1].…”
mentioning
confidence: 99%